A Review of Empirical Research on Transformational Leadership in University Students (2014-2023) - Quiñones Gonzales, Linda Giovanna (2023)
There were analyzed empirical researches on transformational leadership in undergraduate and graduate university students from Peru and abroad between 2014 and 2023. The sample consisted of 23 research articles obtained from five electronic database: ERIC, ScienceDirect, Scopus, PubMed and Alicia. The PRISMA 2020 Declaration was applied to carry out the systematic review of the proposed topic. It was found that the United States is the country from which the main authors who published the most on the subject (30.43%), 2021 was the year with the most publications (26.08%), the most used approach and design were the quantitative (69,6%) and correlational (42.86%) respectively. The most used instruments to measure transformational leadership were the Multifactor Leadership Questionnaire (MLQ) by Bass & Avolio (1990) and the Leadership Practice Inventory (LPI) by Kouzes & Posner (2012). Additionally, an overview of the psychometric properties of the instruments applied and the statistics used by the researchers of the selected studies was presented. Finally, some recommendations were provided to continue the development of the topic addressed.